BENTUK, FUNGSI DAN MAKNA JODOUSHI {~NAKEREBANARAI}, {~BEKIDA} DAN {~ZARU O ENAI } DALAM NOVEL TOBU GA GOTOKU VOLUME 1-10 KARYA RYOUTAROU SHIBA - Ni Wayan, Rusprianti (Humanis; Volume 12. No.2. Agustus 2015, 2015)
This research analized the “form, function and meaning, and subtitution of jodoushi {~nakerebanaranai}, {~bekida} and {~zaru o enai} in the novel Tobu ga Gotoku volume 1-10 written by Ryoutarou Shiba”. The theory which were used referred to the opinions of Sakata an Kuramochi (1993) dan Makino and Tsutsui (1989&1995). The result of this research shown that jodoushi {~nakerebanaranai} contains the meaning of necessity on an obligation. Jodoushi {~bekida} contains the meaning of necessity for opponents about the hope of something happen. Jodoushi {~zaru o enai} contains the meaning of necessity that have to be performed when there is no other choices except have to doing something. In the other hand, jodoushi {~zaru o enai} can be replace by jodoushi {~nakerebanaranai} when it mean is must to do something because no more choise anymore. Jodoushi {~zaru o enai} cannot be replacing jodoushi {~nakerebanaranai} when it show a necessity based on obligation.
Keywords: jodoushi {~nakerebanaranai},{~bekida} and {~zaru o enai}